From Marxist Feminism to Queer Materialist Theory: Conceptualizing Gender as Social Form - Chiara Stefanoni Francesco Aloe, (Bollettino Filosofico, 2025)
This article contributes to the renewed inquiry into the relationship between Marxism and feminism by addressing a core omission in traditional Marxist theory: the analysis of the social forms through which individuals are reproduced, alongside goods and services. Building on Marxist feminist critiques and Marx and Engels’s early insights, it develops a novel materialist queer theory. First, it rethinks the gender–capital relation via revisiting the 1970s Marxist feminist notion of the “extended mode of production”. Second, it conceptualizes gender as a social form, drawing on Gayle Rubin’s sex/gender system and queer critiques of heterosexuality by Judith Butler and Teresa De Lauretis. Third, integrating Foucault’s analysis of the dispositif of sexuality, it demonstrates the historical necessity of gender as the form of production of individuals in capitalist societies. Keywords: Feminism, Gender, Marx, Materialism, Queer Theory